2000
DOI: 10.1557/proc-636-d1.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo Simulation of Amphiphile Self-Assembly during Dip Coating

Abstract: Fascinating nanostructured porous materials have recently been synthesized by evaporation-driven coassembly of ceramic precursors and amphiphiles. To expand our understanding of this process, we examine the influence of interfaces on self-assembly process using equilibrium lattice-based Monte Carlo simulations of ternary amphiphile-solvent mixtures. The simulations are able to predict the existence of all significant lyotropic mesophases, including lamellae, hexagonal closepacked cylinders, and cubic phases su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 12 publications
1
19
0
Order By: Relevance
“…By analogy with surface chemistry strategies used to orient block copolymer films, the Rankin group has reported the synthesis of mesoporous titania thin films with o-HCP cylindrical nanopores using EISA with P123 (a triblock copolymer with the composition HO­(CH 2 CH 2 O) x ­(CH 2 CH­(CH 3 )­O) y ­(CH 2 CH 2 O) x H, where, on average, x = 20 and y = 70) as structure directing agent and titanium­(IV) ethoxide as titania precursor. , The hypothesis underlying this approach is that orthogonal alignment of the HCP mesophase can be achieved in a EISA-derived ceramic film by modifying the substrate surface so that it interacts equally with both blocks of the P123 template, making it chemically “neutral” toward the template surfactant. Monte Carlo simulations , have shown that this is the expected outcome for mixtures of surfactants and small molecules, and not just for neat block copolymers . A related epitaxial orientation procedure was demonstrated by Tolbert and co-workers, where HCP film was cast onto a cubic template film to induce orthogonal alignment .…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…By analogy with surface chemistry strategies used to orient block copolymer films, the Rankin group has reported the synthesis of mesoporous titania thin films with o-HCP cylindrical nanopores using EISA with P123 (a triblock copolymer with the composition HO­(CH 2 CH 2 O) x ­(CH 2 CH­(CH 3 )­O) y ­(CH 2 CH 2 O) x H, where, on average, x = 20 and y = 70) as structure directing agent and titanium­(IV) ethoxide as titania precursor. , The hypothesis underlying this approach is that orthogonal alignment of the HCP mesophase can be achieved in a EISA-derived ceramic film by modifying the substrate surface so that it interacts equally with both blocks of the P123 template, making it chemically “neutral” toward the template surfactant. Monte Carlo simulations , have shown that this is the expected outcome for mixtures of surfactants and small molecules, and not just for neat block copolymers . A related epitaxial orientation procedure was demonstrated by Tolbert and co-workers, where HCP film was cast onto a cubic template film to induce orthogonal alignment .…”
Section: Introductionmentioning
confidence: 80%
“…84,85 The hypothesis underlying this approach is that orthogonal alignment of the HCP mesophase can be achieved in a EISA-derived ceramic film by modifying the substrate surface so that it interacts equally with both blocks of the P123 template, making it chemically "neutral" toward the template surfactant. Monte Carlo simulations 86,87 have shown that this is the expected outcome for mixtures of surfactants and small molecules, and not just for neat block copolymers. 82 A related epitaxial orientation procedure was demonstrated by Tolbert and co-workers, where HCP film was cast onto a cubic template film to induce orthogonal alignment.…”
Section: ■ Introductionmentioning
confidence: 88%
“…With the continuous diffusion and re‐assembly of CTAB molecules, newly hydrolyzed silicate oligomers are adsorbed and cross‐linked onto the charged micelle head groups at the solution–silica film interface, leading to a continuous, large‐domain film growth along with the longitudinal direction of cylindrical micelles that are perpendicularly orientated on the substrate (step 4). Previously reported Monte Carlo simulation results also showed that a highly active interface induces a perpendicular alignment in surfactant mesophases 44. After solution assembly and growth, mesoporous silica films with perpendicular channels are subsequently obtained through the removal of surfactants by solvent extraction (step 5).…”
mentioning
confidence: 94%
“…This approach strikes a good balance between molecular detail and the ability to routinely witness spontaneous self-assembly processes on an acceptable computational time scale. 24 The particular implementation here represents the small molecules as a simple lattice gas, single beads occupying single sites. Our surfactants are linear chains (H 2 T 6 ) of 2 headgroup beads and 6 tail group beads, together occupying 8 sites.…”
Section: Resultsmentioning
confidence: 99%